Pengembangan Usaha Cafe Herbal di Desa Sentra Kelor Bogo: Herbal Cafe Business Development in Sentra Kelor Village, Bogo - Karina Citra Rani; Elsye Tandelilin; Nikmatul Ikhrom Eka Jayani; Noviaty Kresna Darmasetiawan; Johan Sukweenadhi; Prayogo Widyastoto Waluyo; Ummy Maisarah Rasyidah; Nani Parfati (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The millennial herbal café could create a taste of Jammu that was acceptable to millennials by processing Jammu using various techniques and combining it with other ingredients that were beneficial for the body. The community service activities carried out were aimed at developing the Café Herbal business, which produces processed millennial herbal products that were liked by customers. The methods chosen as follow-up are training, mentoring, and comparative studies. Evaluation of training and mentoring was seen by using a questionnaire given as a post-test and the success of Partners in producing Millennial herbal preparations. The Ubaya team created an herbal corner and scheduled an herbal corner training including the manufacture of millennial herbal drinks/herbal drinks, quality aspects of herbal drinks, business opportunities, and step-by-step development of herbal corners and comparative studies at Cafés with the millennial herbal concept. From community service activities, a contemporary booth for the herbal corner has been produced, which is equipped with a neon sign box and café tools. The training that has been carried out has an impact on increasing partner knowledge (63% of participants showed good understanding). The increase was shown by several millennial herbal drink menus produced, including “Blue tea milky” (infusion of butterfly pea flowers and milk), “Red ginger milky” (red ginger and milk), and “Green silky milky” (moringa leaf powder and milk). ABSTRAK Café jamu milenial mampu menciptakan rasa Jamu yang dapat diterima oleh milenial dengan mengolah Jamu menggunakan berbagai teknik dan dipadukan dengan bahan-bahan lain yang bermanfaat bagi tubuh. Kegiatan pengabdian masyarakat yang dilakukan bertujuan untuk mengembangkan usaha Café Herbal yang menghasilkan produk olahan jamu milenial yang disukai pelanggan. Metode yang dipilih sebagai tindak lanjut yaitu pelatihan, pendampingan dan studi banding. Evaluasi keberhasilan pelatihan dan pendampingan dilihat dengan menggunakan kuesioner yang diberikan sebagai post test dan keberhasilan Mitra dalam menghasilkan olahan jamu milenial. Tim Ubaya merealisasikan pembuatan herbal corner dan mengagendakan serangkaian pelatihan diantaranya pembuatan minuman herbal/jamu milenial, aspek mutu dari minuman herbal, peluang usaha serta step by step pengembangan herbal corner dan studi banding pada Café dengan konsep jamu milenial. Dari kegiatan pengabdian masyarakat telah dihasilkan booth kekinian untuk herbal corner yang dilengkapi neon box penanda dan alat-alat café. Pelatihan-pelatihan yang telah dilakukan memberikan dampak peningkatan pengetahuan Mitra (63% peserta menunjukkan hasil pemahaman yang baik). Peningkatan ketrampilan ditunjukkan dengan beberapa menu minuman jamu milenial yang dihasilkan diantaranya “Blue tea milkymo” (seduhan bunga telang dan susu), “Red ginger milkymo” (Jahe merah dan susu) dan “Green silky milkymo” (serbuk daun kelor dan susu).